En-Gendering Economic Inequality - Gilman, Michelle E. (Columbia Journal of Gender and Law, 2016)
We live in an era of growing economic inequality. Luminaries ranging from the President to the Pope to economist Thomas Piketty in his bestselling book Capital in the Twenty- First Century have raised alarms about the disparity between the haves and the have-nots. Overlooked, however, in these important discussions is the reality that economic inequality is not a uniform experience; rather, its effects fall more harshly on women and minorities. With regard to gender, American women have higher rates of poverty and get paid less than comparable men, and their workplace participation rates are falling. Yet economic inequality is neither inevitable nor intractable. Given that the government creates the rules of the market, it is essential to analyze the government’s role in perpetuating economic inequality. This Article specifically examines the role of the Supreme Court in contributing to gender- based economic inequality. The thesis is that the Supreme Court applies oversimplified economic assumptions about the market in its decision-making, thereby perpetuating economic inequality on the basis of gender. Applying insights of feminist economic theory, the Article analyzes recent Supreme Court jurisprudence about women workers, including Wal-Mart v. Dukes (denying class certi cation to female employees who were paid and promoted less than men), Burwell v. Hobby Lobby Stores, Inc. (granting business owners the right to deny contraception coverage to female employees on religious grounds), and Harris v. Quinn (limiting the ability of home health care workers to unionize and thereby improve their working conditions). In these cases, the Court elevates its narrow view of efficiency over more comprehensive understandings, devalues care work, upholds harmful power imbalances, and ignores the intersectional reality of the lives of low-wage women workers. The Article concludes that the Court is eroding collective efforts by women to improve their working conditions and economic standing. It suggests advocacy strategies for reforming law to obtain economic justice for women and their families.